The Taylor Rule in Theory and Practice : Analysing CNB’s Policy in the Context of Czechia’s 2022 Inflation Spike - Král, Milan; Potužák, Pavel; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines whether the Czech National Bank’s (CNB) monetary policy between 2017 and 2024 aligned with Taylor rule prescriptions, with a focus on the 2022 inflation surge. Using data from 1996 to 2024, the study estimates potential output via a linear trend, the Hodrick-Prescott filter, and the CNB’s production function to construct output gaps and calculate Taylor rule-consistent interest rates. The analysis finds that the CNB deviated significantly from the rule, particularly by tightening too slowly during the inflation build-up in 2021–2022 and maintaining lower-than-implied rates until late 2023. Since early 2024, by contrast, the CNB has kept interest rates above rule-based recommendations. These findings illustrate the risks of relying on discretionary policy in times of uncertainty and suggest that a more strategic approach might have supported earlier action and improved inflation control. The thesis concludes that while full adherence to a simple rule may not be realistic, the Taylor rule remains a useful reference for evaluating and guiding policy – particularly if Czechia remains an independent monetary regime outside the eurozone.
Vedoucí práce: Pavel Potužák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses